Simultaneous MLPA-based multiplex point mutation and deletion analysis of the dystrophin gene. - Bunyan, D; Skinner, A; Ashton, E; Sillibourne, J; Brown, T; Collins, A; Cross, N; Harvey, J; Robinson, DO (2007)
The Multiplex Ligation-dependent Probe Amplification assay (MLPA) is the method of choice for the initial mutation screen in the analysis of a large number of genes where partial or total gene deletion is part of the mutation spectrum. Although MLPA dosage probes are usually designed to bind to normal DNA sequence to identify dosage imbalance, point mutation-specific MLPA probes can also be made. Using the dystrophin gene as a model, we have designed two MLPA probe multiplexes that are specific to a number of commonly listed point mutations in the Leiden dystrophin point mutation database (http://www.dmd.nl). The point mutation probes are designed to work simultaneously with two widely used dystrophin MLPA multiplexes, allowing both full dosage analysis and partial point mutation analysis in a single test. This approach may be adapted for other syndromes with well defined common point mutations or polymorphisms.